Association Between Neutrophil-to-Lymphocyte Ratio with Inflammatory Activity and Fibrosis in Non-alcoholic Fatty Liver Disease - WenYi, Jin; Ting, Qian; PiaoPiao, Ying; JinMing, Wu (Turkish Journal of Gastroenterology, 2022)
Background: Inflammation plays an important role in the development and progression of non-alcoholic steatohepatitis (NASH), andNASH is a powerful driving force for the progression of fibrosis. The neutrophil-to-lymphocyte ratio (NLR) is a simple emerging indicatorof inflammation. We aimed to assess the potential association between NLR and histological severity of non-alcoholic fatty liver disease(NAFLD).Methods: This retrospective study consisted of 231 patients with biopsy-proven NAFLD in China from August 2017 to September 2019.The steatosis, activity, and fibrosis scoring system were used to evaluate liver biopsy tissue.Results: Of the 231 patients with NAFLD, advanced inflammatory activity was present in 43.3% and significant fibrosis in 25.5% ofpatients. Multivariate logistic regression analysis showed NLR to be correlated with advanced inflammatory activity (Odds ratio (OR):0.62, 95% CI: 0.42-0.94, P = .025) and significant fibrosis (OR: 0.57, 95% CI: 0.35-0.94, P = .028). The NLR was inversely associated withthe degree of steatosis, lobular inflammation and fibrosis (r = −0.16, P = .014; r = −0.15, P = .019; r = −0.13, P = .046, respectively), buthad no association with the severity of ballooning. The multivariate-adjusted models had good predictability for advanced inflammatoryactivity (area under curves (AUC) 0.790, 95% CI: 0.730-0.850) and for significant fibrosis (AUC 0.798, 95% CI: 0.728-0.868).Conclusion: This study showed negative correlations between elevated NLR levels with advanced inflammatory activity and significantfibrosis in patients with NAFLD. Our results also suggested that NLR could be considered as a simple and noninvasive mark to identifyhigh-risk populations in NAFLD.